(untitled) (Research, Society and Development, 2024)
Tourism is a complex socioeconomic activity, susceptible to internal challenges such as crime and violence. In view of this, primary prevention emerges as the most genuine and efficient way to address the criminal phenomenon, targeting the entire population. It refers to strategies and interventions aimed at eliminating or reducing the conditions that foster the occurrence of criminal activities before they manifest. In this context, the central objective of this study was to analyze the benefits of implementing primary prevention measures regarding violence in the region of the Ecological Route of Miracles, on the Northern Coast of Alagoas. For this purpose, exploratory and descriptive research was adopted as a methodological design, through a bibliographic review, as well as the application of forms to military personnel and municipal managers. As a result, it was found that the effective implementation of primary violence prevention strategies in the region of the Ecological Route of Miracles requires the commitment and collaboration of all actors involved, including security forces, municipal managers, local communities, and the private sector. Furthermore, it was identified that by adopting an integrated and evidence-based approach, it is possible to promote a safe and welcoming environment that stimulates sustainable socioeconomic development and the well-being of all individuals who live and visit the region.